Auditor-provided tax services and long-term tax avoidance. Issue 3 (10th August 2015) - Hogan, Brian; Noga, Tracy
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to determine the association between auditor-provided tax services (APTS) and long-term corporate tax rates. Design/methodology/approach – The paper uses empirical data and multivariate regression models to explore the relationship between a firm's use of APTS and their long-term effective tax rate. Findings – An economically and statistically significant long-term negative relationship was found between firm levels of APTS and taxes paid. Further, a portion of this benefit is lost for some firms when returning to their auditor for tax services even after a short break. Originality/value – This paper contributes to the debate regarding the value of APTS by providing evidence of the apparent long-term negative consequences to firms who reduce their reliance on APTS, perhaps even through the engagement of separate accounting firms for their audit and tax functions, although these consequences may be mitigated upon return with a significant increase in APTS. However, this is the first study, to our knowledge, to explore, in a long-term setting, the consequences of a firm's return to their auditors for a non-audit service previously reduced or terminated. Additionally, further incremental contributions are made to other studies that look at APTS and tax avoidance by studying the long-term relationship which allows firms to consider the cumulative cost/benefit relationship between independence and knowledge spillover.